Peran Kepemimpinan dalam Implementasi Pengawasan Kepada Kinerja Pegawai pada Dinas Tenaga Kerja dan Transmigrasi di UPTD Balai Wasnaker Wilayah 1 - Bagas Putra Wicaksana; Moh. Ihsan; Dessy Elliyana (EBISMAN eBisnis Manajemen, 2026)
The Role of Leadership in the Implementation of Employee Performance Supervision at the Manpower and Transmigration Office at the Regional Manpower Supervisory Agency (UPTD) for Regional Manpower Supervisory Agency (Balai Wasnaker) 1. This study aims to determine the role of leadership in the implementation of employee performance supervision. Effective leadership is an important factor in ensuring that employees perform their duties and responsibilities in accordance with organizational goals and established regulations. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. Informants were selected based on their involvement in supervision activities and understanding of employee performance management. The results indicate that leadership plays a significant role through direction, coaching, monitoring, and evaluation of employee performance. Employee performance is generally quite good, but supervision has not been optimal due to limited time, diverse tasks, and inconsistent evaluation follow-up. In addition, communication and coordination between leaders and employees influence the effectiveness of supervision. Therefore, the implementation of leadership-supported supervision has a positive impact on employee discipline, responsibility, and work effectiveness, but there is still a need for improvement in the consistency of employee supervision and coaching to achieve optimal organizational performance.